EVALUATION OF HEATED CHICKEN EGGSHELL POWDER AS ANTIBACTERIAL AGAINST ESBL (EXTENDED SPECTRUM BETA LACTAMASE) PRODUCING Escherichia coli: IN-VITRO AND IN-SILICO STUDIES - Fajar Nugraha; Hariyanto IH; Hadi Kurniawan; Siti Nani Nurbaeti; Inarah Fajriaty; Aldi Priady (BRIN Publishing (Penerbit BRIN), 2026)
Antimicrobial resistance (AMR) has become a critical global health concern, particularly with the increasing prevalence of Extended-Spectrum β-Lactamase (ESBL)-producing Escherichia coli. This study aimed to evaluate the antibacterial activity of heated chicken eggshell powder (HCEP) against ESBL-producing E. coli through both in-vitro and in-silico approaches. The In-silico molecular docking studies revealed that calcium diglyceroxide exhibited the strongest binding affinity toward dihydrofolate reductase –5.9 kcal/mol, suggesting disruption of folate metabolism as a potential antibacterial mechanism. Meanwhile, in vitro results demonstrated measurable antibacterial activity, with inhibition zones ranging from 6.90 to 12.36 mm and minimum inhibitory concentration (MIC) values of 1.421 µg/ml for non-ESBL and 2.842 µg/ml for producing-ESBL E. coli. The antibacterial effect was attributed to calcium oxide content, which generates reactive oxygen species (ROS) and induces a highly alkaline microenvironment. The correlation analysis showed a strong positive relationship between sample concentration and inhibition zone as antibacterial against E. coli producing-ESBL (r = 0.987). These suggest that increasing the concentration of the HCEP sample results in a larger inhibition zone. Overall, these findings highlight HCEP as a potential alternative antibacterial agent, particularly in topical applications, while also offering a sustainable approach to eggshell waste utilization.